A study of vibration features for rotating specimenunder cyclic loading - Nazirul Azim, Mohd Asri (2013)
This thesis presented about a study of vibration features for rotating specimen under cyclic loading. From statistical, about 90% of the machines are a failure due to fatigue phenomena, thus need to monitor the fatigue behaviour on component (early detection) to avoid machine breakdown. The main objectives of the project are to measure vibration response during cyclic loading and study the response under frequency domain analysis. The equipment involves are fatigue testing machine, accelerometer, and data acquisition (DAQ). The position of the accelerometer was placed near to the bearing housing. Then, create a block module using DASYLAB software to record the data. Result shows, signal at y-axis are dominant compared to the x-axis and z-axis. Signal value at y-axis is higher because of force applied are parallel to the y-axis that perpendicular to the specimen (vertical axis displacement). Signal at x-axis is lowest compare to the others axis, because at x-axis is parallel to the specimen. Thus, from this result more focus on y-axis data. For mild steel, at forces 250 N, the specimen fractured at 7769 cycles with amplitude value is 8.50, followed by 200 N at 23 238 cycle and 150 N at 100 510 cycles with amplitude 7.30 and 5.70 respectively. For low carbon steel, at 250 N the specimen fractured at 9400 cycles with amplitude value 9.59, higher than other load, at 200 N the specimen fractured at 24 300 cycle and 150 N at 137 749 cycles with amplitude value is 7.90 and 7.60, respectively. From the result, with constant force applied, the value of amplitude increase when the number of cycle increases. This is because, the power that transmits from the motor to the specimen will reduce the stiffness on the specimen, and the resistance will decrease. This increased loads can accelerate crack growth and ultimate failure can affect the changing amplitude for the specimen.